Composite particles, method for producing composite particles, negative electrode active material for secondary battery, negative electrode and secondary battery
Patent Information
- Application Number
- JP2024529986
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-02
- Filing Date
- 2024-02-15
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2044-02-15
AI Technical Summary
【0014】 本発明の複合粒子は、表面副反応を抑制することができ、二次電池における容量維持率や初回クーロン効率といった充放電性能を高く維持できる。また、本発明の複合粒子は、大気中で長時間保管した際に二次電池としたときの初期効率などが低下せず、品質安定性を有する。
Smart Images

Figure 0007632757000001 
Figure 0007632757000002 
Figure 0007632757000003
Abstract
Description
Technical Field
[0001] The present invention relates to composite particles, a method for producing the composite particles, a negative electrode active material for a secondary battery containing the composite particles, a negative electrode containing the negative electrode active material, and a secondary battery containing the negative electrode.
Background Art
[0002] Due to environmental considerations in energy demand, the development of electric vehicles (EVs) has been rapidly progressing, and the range of use of lithium-ion batteries (LIBs) is expanding. Graphite, which is the mainstream of LIB negative electrode materials, has a low theoretical capacity density (372 mAh / g). To improve the battery capacity, the development of high-capacity active materials using silicon, tin, and oxides has been actively carried out. However, these materials have a problem that the charge-discharge characteristics deteriorate because the active material is pulverized by repeated charge-discharge due to large volume expansion and contraction accompanying the insertion and extraction of lithium ions.
[0003] Patent Document 1 describes a negative electrode active material comprising a carbonaceous matrix containing a plurality of nanoparticles, wherein the nanoparticles include a silicon core, an oxide film layer disposed on the silicon core and containing SiOx (0 < x ≤ 2), and a coating layer containing LiF covering at least a part of the surface of the oxide film layer.
[0004] Patent Document 2 describes a negative electrode active material particle having a negative electrode active material particle containing silicon compound (SiOx: 0.5 ≤ x ≤ 1.6) particles, wherein at least a part of the negative electrode active material particle is coated with a carbon material and contains one or more selected from Li2SiO3 and Li2Si2O5, and when the negative electrode active material particle is measured by X-ray diffraction using Cu-Kα rays, the intensity Ia of the peak near 2θ = 28.4° attributed to the Si crystal structure obtained by the X-ray diffraction, the peak intensity Ib of the peak attributed to Li2SiO3 obtained by the X-ray diffraction, and the peak intensity Ic of the peak attributed to Li2Si2O5 obtained by the X-ray diffraction satisfy Ib / Ia ≤ 4.8 and Ic / Ia ≤ 6.0.
[0005] Patent Document 3 describes a Si-OC-Li composite comprising nanosilicon, a silicon-oxygen-lithium compound, and a carbon coating, the silicon-oxygen-lithium compound being partially crystallized, the composite further comprising silicon oxide, the composite comprising nanosilicon dispersed in the silicon-oxygen-lithium compound to form fused particles, the fused particles dispersed in a matrix of silicon oxide in an islands-in-a-sea form to form composite particles, and a carbon coating covering the surfaces of the composite particles. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Publication No. 2022-125285 [Patent Document 2] Japanese Patent Application Publication No. 2020-113495 [Patent Document 3] Japanese Patent No. 7094957 Summary of the Invention [Problem to be solved by the invention]
[0007] However, the negative electrode active material described in Patent Document 1 has LiF coated on Si particles, which may not be able to withstand the silicon expansion caused by the absorption and release of lithium ions. In order to suppress such Si expansion, it is considered necessary to provide a structure such as a matrix phase.
[0008] In the negative electrode active material of Patent Document 2, Li needs to be sufficiently diffused to the inside in order to improve performance, but this requires an increased amount of Li to be added. Increasing the amount of Li added leads to increased costs, and the initial efficiency of the secondary battery may decrease when stored in air for a long period of time. Therefore, it is preferable to reduce the amount of Li added as much as possible. In addition, in order to improve performance, it is necessary to control the structure of the active material with a small amount of Li. Specifically, it is preferable for Li to be selectively present on the surface of the active material, which suppresses surface side reactions with the electrolyte and improves battery performance.
[0009] The composite described in the above Patent Document 3 is only a silicon-oxy-lithium compound, silicon oxide, and carbon coating, which cannot withstand the expansion inhibition of Si. In addition, Patent Document 3 states that "the obtained composite has a stable structure, and can effectively prevent components such as air from penetrating into the particle and causing the active component to become ineffective, and the structure and properties do not deteriorate even when stored for a long period of time," but this is not verified by quantitative evaluation in the examples, and it cannot necessarily be said that the quality is stable even when stored for a long period of time as described above.
[0010] In the conventional techniques described in the above Patent Documents 1 to 3, only SiO2 or LixSiyOz exists around the Si particles, which may not be sufficient to suppress the expansion of Si. In order to improve the charge / discharge characteristics, it is necessary to control the metal element concentration inside the active material, and further, in order to suppress the surface side reaction with the electrolyte, it is necessary to control the structure of the active material surface.
[0011] The present invention aims to provide composite particles that can suppress surface side reactions with an electrolyte and Si expansion during repeated charging and discharging, and can further improve the initial charge-discharge efficiency and cycle characteristics of the active material, a method for producing the composite particles, a negative electrode active material for a secondary battery containing the composite particles, a negative electrode containing the negative electrode active material, and a secondary battery containing the negative electrode.The present invention also aims to provide composite particles and a negative electrode active material for a secondary battery containing the same, which are stable in quality and do not decrease in initial efficiency when used as a secondary battery when stored in air for a long period of time by controlling the amount of Li added. [Means for solving the problem]
[0012] As a result of intensive research to solve the above problems, the present inventors have found that a composite particle structure containing a matrix phase containing Si and O elements that suppresses the expansion of Si during charging and discharging and a specific metal silicate can be produced. Furthermore, they have found that by controlling the concentration of the metal part of this metal silicate and selectively distributing the metal element, side reactions on the surface can be suppressed, leading to improved charge and discharge performance.
[0013] The present invention has the following aspects. [1] Composite particles comprising at least one silicon particle and a matrix phase containing Si and O elements outside the silicon particle, and further containing a silicate compound, the silicate compound containing at least one metal element selected from the group consisting of Li, K, Na, Ca, Mg, and Al. [2] The composite particle according to [1], wherein the metal ion element concentration of the metal element is 0.1 to 40.0 atom % based on the total elements of the composite particle. [3] When the ratio A of the metal ion element to all elements present in a region of 30% from the surface of the composite particle in the inward direction is taken as A, and the ratio B of the metal ion element to all elements present in the other region is taken as B, the metal ion element abundance ratio is 0.5 [4] The composite particle according to any one of [1] to [3], wherein the silicate compound contains Li element. [5] The composite particles according to any one of [1] to [4], wherein the silicate compound has a crystal structure represented by LixSiyOz (where x, y, and z are integers greater than 0). [6] The composite particles according to any one of [1] to [5], wherein the silicate compound has a crystal structure represented by LixSiyOz (satisfying x + 4y - 2z = 0). [7] The composite particles according to any one of [1] to [6], wherein the silicate compound has a crystal structure including at least one selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5. [8] The composite particles according to any one of [1] to [7], wherein the Li element is 20% by mass or less based on the total mass of the composite particles. [9] The composite particles according to any one of [1] to [8], wherein the peak intensity C corresponding to the (111) plane of the silicon particles in the X-ray diffraction spectrum of the silicon particles and the peak intensity D corresponding to the (111) plane in the X-ray diffraction spectrum of Li2SiO3 satisfy 0 < D / C ≦ 0.6.
[10] The composite particles according to any one of [1] to [9], wherein in the peak corresponding to the (111) plane of the silicon particles in the X-ray diffraction spectrum of the silicon particles, the crystallite size x satisfies 10 nm < x < 30 nm, and in the X-ray diffraction peak corresponding to the (111) plane of Li2SiO3, the crystallite size y satisfies 1 nm < y < 40 nm.
[11] The composite particles according to any one of [1] to
[10] , wherein the average particle size x satisfies 1 μm < x < 15 μm, and the specific surface area n satisfies 0.1 m 2 / g < n < 20 m 2 / g.
[12] The composite particles according to any one of [1] to
[11] , wherein the matrix phase contains Si and O elements, and also C element.
[13] A method for producing the composite particles according to any one of [1] to
[12] , including the following Step 1 and Step 2. Step 1: A step of mixing at least one metal element compound selected from the group consisting of Li, K, Na, Ca, Mg, and Al with an intermediate derived from a polysiloxane resin containing silicon particles Step 2: Firing at 900°C or less in an oxygen-free atmosphere
[14] A negative electrode active material for a secondary battery, comprising the composite particles according to any one of [1] to
[12] .
[15] A negative electrode comprising the negative electrode active material for a secondary battery according to
[14] .
[16] A secondary battery comprising the negative electrode according to
[15] . Effect of the Invention
[0014] The composite particles of the present invention can suppress surface side reactions and can maintain high charge / discharge performance such as capacity retention rate and initial coulombic efficiency in a secondary battery. Furthermore, the composite particles of the present invention have quality stability and do not decrease in initial efficiency when used as a secondary battery after long-term storage in air. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, embodiments of the present invention will be described in detail. In this specification, "mass" is synonymous with "weight." In addition, in this specification, unless otherwise specified, the numerical range "to" is used to mean that the numerical range includes the numerical range before and after it as the lower limit and upper limit.
[0016] [Composite particles] The composite particle of this embodiment has at least one silicon particle and a matrix phase containing Si and O elements outside the silicon particle, and further contains a silicate compound, and the silicate compound contains at least one metal element selected from the group consisting of Li, K, Na, Ca, Mg, and Al. The composite particle of the present embodiment is characterized in that a plurality of silicon particles are dispersed and embedded in a matrix phase, and further in that the silicate compound is distributed as a component. The silicate compound may be present outside the matrix phase as a silicate layer, or may be present inside the silicon particles or the matrix phase, or may be both.
[0017] (silicon particles) The silicon particles in the composite particles of this embodiment are composed of silicon with a valence of 0 and have an average particle size of 300 nm or less. The average particle size of the silicon particles is preferably 5 nm to 300 nm, more preferably 20 nm to 250 nm, and even more preferably 50 nm to 200 nm. When the average particle size of the silicon particles is within this range, charge and discharge performance such as the capacity retention rate and the initial Coulomb efficiency in a secondary battery can be maintained at a high level. Note that the average particle size of the silicon particles is obtained by observing the composite particles of this embodiment by TEM and obtaining the average value of the particle sizes of 50 silicon particles arbitrarily selected from a TEM image at a magnification of 50,000 times.
[0018] It is preferable that for the silicon particles constituting the composite particles of this embodiment, the peak intensity C corresponding to the (111) plane of the silicon particles in the X-ray diffraction spectrum and the peak intensity D corresponding to the (111) plane in the X-ray diffraction spectrum of Li2SiO3 satisfy 0 < D / C ≤ 0.6. A range of 0.05 < D / C ≤ 0.5 is more preferable. When this peak intensity range is satisfied, charge and discharge performance such as the capacity retention rate and the initial Coulomb efficiency in a secondary battery can be maintained at a high level.
[0019] In the peak where 2θ in the above X-ray diffraction spectrum corresponds to the (111) plane of the silicon crystal structure, the crystallite size x obtained by Scherrer formula calculation using the peak half-width is 10 nm < x < 30 nm, and in the X-ray diffraction peak corresponding to the (111) plane of Li2SiO3, it is preferable that the crystallite size y is 1 nm < y < 40 nm. When the crystallite size satisfies this range, charge and discharge performance such as the capacity retention rate and the initial Coulomb efficiency in a secondary battery can be maintained at a high level.
[0020] From the viewpoints of charge-discharge capacity, initial Coulomb efficiency, and cycle characteristics, the specific surface area of the above silicon particles is 50 m 2 / g to 400 m 2 / g is preferable, 100 m 2 / g to 300 m 2 / g is more preferable, and 150 m 2 / g to 230 m 2 / g is more preferable. The specific surface area is a value determined by the BET method, can be determined by nitrogen gas adsorption measurement, and can be measured using, for example, a specific surface area measuring device. Further, in order to remove organic deposits on the silicon particles, it is preferable to perform heat treatment at 500 °C for 2 hours in a nitrogen atmosphere before measuring the specific surface area.
[0021] The form of the above silicon particles is not particularly limited, and may be, for example, granular, acicular, or flaky. However, from the viewpoint of charge-discharge performance when used as a secondary battery, the length in the major axis direction is preferably 30 nm to 300 nm, and the thickness is preferably 1 nm to 60 nm. From the viewpoint of charge-discharge performance when used as a secondary battery, a needle-like or flaky shape with an aspect ratio, which is the ratio of thickness to length, of 0.5 or less is preferable. The form of the silicon particles can be measured for the average particle size by the dynamic light scattering method. However, by using analysis means such as a transmission electron microscope (TEM) or a field emission scanning electron microscope (FE-SEM), samples with an aspect ratio can be identified more easily and precisely. In the case of silicon particles, the sample can be cut by a focused ion beam (FIB) to observe the cross section by FE-SEM, or the sample can be sliced and the state can be identified by TEM observation. The aspect ratio of the silicon particles is a calculation result based on 50 particles of the main part of the sample within the field of view shown in the TEM image.
[0022] (Matrix phase) The matrix phase existing outside the above silicon particles contains at least Si element and O element. The above matrix phase preferably has a composition represented by SiOx (1 < x < 2), and more preferably contains carbonaceous (C element) as a component. The matrix phase is a three-dimensional network structure of a silicon-oxygen skeleton containing at least silicon and oxygen elements. It is also preferable that the matrix phase contains silicon, carbon, and oxygen elements and is a three-dimensional network structure of a silicon-oxygen-carbon skeleton. This three-dimensional network structure of a silicon-oxygen-carbon skeleton has relatively high chemical stability, has a composite structure with carbon (carbonaceous phase), and exhibits small volumetric changes with respect to the absorption and release of lithium. In particular, it is preferable that the three-dimensional network structure of the matrix phase contains a silicon oxycarbide (SiOC) structure. This three-dimensional network structure may contain a nitrogen element in addition to silicon, carbon, and oxygen elements.
[0023] (Silicate compounds) The above-mentioned silicate compounds are generally compounds containing an anion having a structure in which one or more silicon atoms are at the center and electronegative ligands surround the silicon atom, and the silicate compounds containing at least one metal (element) selected from the group consisting of Li, K, Na, Ca, Mg, and Al are salts of these metals and compounds containing anions.
[0024] Examples of compounds containing the above anions include orthosilicate ions (SiO4 4- ), metasilicate ion (SiO3 2- ), pyrosilicate ion (SiO7 6- ), cyclic silicate ion (Si3O9 6- or SiO 18 12- ) and other silicate ions.
[0025] The silicate compound is preferably a lithium silicate compound, a magnesium silicate compound, or a sodium silicate compound, more preferably a lithium silicate compound or a magnesium silicate compound, and particularly preferably a lithium silicate compound.
[0026] Lithium silicate compounds include Li x S y O z(where x, y, z are integers greater than 0), and Li x S y O z It is more preferable that the lithium silicate compound contains a crystal structure represented by (x+4y-2z=0). Examples of such lithium silicate compounds include lithium metasilicate (Li2SiO3, Li2Si2O5, Li4SiO4), and it is preferable that the lithium silicate compound contains at least one crystal structure selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5.
[0027] Examples of magnesium silicate compounds include magnesium metasilicate (MgSiO 3、 Mg2SiO4).
[0028] Examples of sodium silicate compounds include sodium metasilicate (Na2SiO3, Na4SiO4, Na2Si2O5, Na2Si4O9).
[0029] The silicate compound may have two or more of the above metals. When it has two or more metals, one silicate ion may have a plurality of metals, or it may be a mixture of silicate compounds having different metals. The silicate compound may also have a metal other than the above metals. When the silicate compound is in a crystalline state, it can be detected by powder X-ray diffraction measurement (XRD), and when it is amorphous, it can be detected by powder X-ray diffraction measurement (XRD). 29 This can be confirmed by Si-NMR measurement.
[0030] The content of the metal element is preferably 25% by mass or less, more preferably 0.1 to 20% by mass, further preferably 0.2 to 18% by mass, and particularly preferably 0.3 to 15% by mass, based on the total mass of the composite particles. When the content of the metal element is within this range, the surface side reaction of the composite particles can be suppressed, and the charge / discharge performance when used as a secondary battery can be further improved. It is preferable that the metal element is not localized as metal ions only in a part of the composite particles, but is uniformly dispersed (distributed). The content of the metal element can be measured, for example, by Auger electron spectroscopy (AES) or an ICP-OES analyzer.
[0031] The silicate compound preferably contains Li element, and the content of Li element is preferably 20 mass% or less, more preferably 0.1 to 19 mass%, further preferably 0.2 to 17 mass%, and particularly preferably 0.3 to 15 mass% based on the total mass of the composite particles. When the content of Li element is within this range, the surface side reaction of the composite particles can be suppressed, and the charge / discharge performance can be further improved when the composite particles are used as a secondary battery.
[0032] In the composite particle of this embodiment, the metal ion element concentration of the metal element in the total elements of the composite particle is preferably 0.1 to 40.0 atom%, more preferably 0.3 to 35.0 atom%, and particularly preferably 0.5 to 30.0 atom%. When the metal ion element concentration is within this range, side reactions on the surface of the composite particle can be suppressed, and the charge and discharge performance when used as a secondary battery can be further improved. The metal ion element concentration of the metal element can also be measured, for example, by Auger electron spectroscopy (AES).
[0033] In the composite particles of the present embodiment, a concentration gradient of the above metal ion element may be present, and it is preferable that the concentration is higher at the surface portion than inside the composite particles. Specifically, when the ratio A of the metal ion element to all the elements present in the region 30% from the surface portion of the composite particles toward the inside and the ratio B of the metal ion element to all the elements present in the other regions are considered, it is preferable that the proportion of the metal ion element satisfies 0.5 < A / (A + B) < 1.0. The proportion of the metal ion element is more preferably 0.6 < A / (A + B) < 0.99, and even more preferably 0.7 < A / (A + B) < 0.98. When the proportion of the metal ion element is within this range, side reactions on the surface can be suppressed, and the charge-discharge performance of the secondary battery can be further improved.
[0034] The average particle size x of the composite particles of the present embodiment is preferably 1 μm < x < 15 μm, more preferably 2 μm < x < 13 μm, and even more preferably 3 μm < x < 10 μm. Also, the specific surface area n is preferably 0.1 m 2 / g < n < 20 m 2 / g, more preferably 0.5 m 2 / g < n < 18 m 2 / g, and even more preferably 0.7 m 2 / g < n < 15 m 2 / g. When the average particle size and the specific surface area of the composite particles are within this range, side reactions on the surface can be suppressed, and the charge-discharge performance of the secondary battery can be further improved. In particular, it is preferable that the average particle size x is 1 μm < x < 15 μm and the specific surface area n is 0.1 m 2 / g < n < 20 m 2 / g.
[0035] [Negative electrode active material for secondary battery] The negative electrode active material for secondary battery of the present embodiment contains the composite particles of the above present embodiment. Although the composite particles of the present embodiment themselves have the performance as a negative electrode active material, the negative electrode active material for secondary battery may have components other than the composite particles.
[0036] The negative electrode active material for secondary batteries may have a carbon layer on the surface of the composite particles. That is, at least a part of the surface of the composite particles may have a carbon coating. The carbon layer (carbon coating) is preferably a coating made of low crystalline carbon. From the viewpoint of improving chemical stability and thermal stability, the amount of the carbon layer (carbon coating) is preferably 0.1% by mass to 30% by mass, more preferably 1% by mass to 25% by mass, and even more preferably 5% by mass to 20% by mass, based on 100% by mass of the composite active material for secondary batteries. The composite active material for secondary batteries may have a carbon layer (carbon coating) on its surface continuously or intermittently. The carbon layer (carbon coating) is preferably formed on the surface of the active material by chemical vapor deposition.
[0037] The true density of the negative electrode active material for secondary batteries is preferably 1.6 g / cm 3 More than 2.6g / cm 3 The true density is set to 1.75 g / cm from the viewpoint of improving the energy density of the resulting secondary battery. 3 More preferably, 1.80 g / cm 3 The above is more preferable. The true density is a value measured using a true density measuring device.
[0038] The average particle size of the negative electrode active material for secondary batteries is preferably 2 μm or more and 15 μm or less. When the average particle size is 2 μm or more, a significant increase in the specific surface area can be suppressed, and when the material is used as a secondary battery, the reversible charge / discharge capacity per unit volume can be improved by suppressing the amount of SEI generated during charging and discharging. Also, when the average particle size is 15 μm or less, the adhesion strength with the current collector is improved, and peeling from the current collector can be suppressed.
[0039] The specific surface area of the negative electrode active material for secondary batteries is 0.1 m 2 / g or more 10m 2 / g or less. The specific surface area is preferably 0.3 m 2 / g or more is more preferable, and 0.5m 2 / g or more is particularly preferred. When the specific surface area is in the above range, the amount of solvent absorbed during electrode preparation can be appropriately maintained, and the amount of binder used to maintain binding properties can also be appropriately maintained. The specific surface area is a value determined by the BET method, and can be determined by nitrogen gas adsorption measurement, for example, using a specific surface area measurement device.
[0040] [Method of manufacturing composite particles] The method for producing composite particles of the present embodiment includes the following steps 1 and 2. Step 1: A step of mixing at least one metal element compound selected from the group consisting of Li, K, Na, Ca, Mg, and Al with an intermediate derived from a polysiloxane resin containing silicon particles. Step 2: Firing at 900°C or less in an oxygen-free atmosphere The composite particles of the present embodiment are not limited to those obtained by the above-mentioned manufacturing method. The description of the manufacturing method below is merely one aspect of the manufacturing method of the composite particles of the present embodiment, and may include steps other than the above-mentioned steps 1 and 2, and the order of steps 1 and 2 is not particularly limited.
[0041] First, the silicon particles used in step 1 are obtained by wet-pulverizing raw silicon. Specifically, the raw silicon is dispersed in a solvent such as an organic solvent in wet-pulverization to obtain a silicon slurry, which is a dispersion of silicon particles. The silicon slurry can be prepared while the raw silicon is pulverized in a wet powder pulverizer. It is preferable to add a dispersant to the organic solvent to promote the pulverization of the raw silicon. Examples of wet-pulverizing devices include a roller mill, a high-speed rotary pulverizer, a container-driven mill, and a bead mill. The preferred range of the average particle size of the silicon particles in the obtained silicon slurry is as described above.
[0042] Examples of the organic solvent include ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and diisobutyl ketone; alcohols such as ethanol, methanol, normal propyl alcohol, and isopropyl alcohol; and aromatics such as benzene, toluene, and xylene.
[0043] The above-mentioned dispersant may be of an aqueous or non-aqueous type, with non-aqueous dispersants being preferred. Examples of non-aqueous dispersants include polymeric types such as polyethers, alcohols, polyalkylene polyamines, and polycarboxylic acid partial alkyl esters, low molecular weight types such as polyhydric alcohol esters and alkyl polyamines, and inorganic types such as polyphosphates. The solid content concentration of silicon particles and dispersants in the silicon slurry is not particularly limited, but is preferably in the range of 5% to 40% by mass, and more preferably 10% to 30% by mass, with the total amount of the solvent, dispersant, and silicon particles being 100% by mass. The amount of dispersant added is preferably in the range of 2% to 60% by mass, and more preferably 5% to 50% by mass, with respect to the total mass of silicon particles.
[0044] Next, the polysiloxane compound and the silicon slurry obtained by the wet grinding are mixed uniformly, and then the solvent is removed, dried, and treated at a high temperature to obtain an intermediate derived from a polysiloxane resin containing silicon particles. Specifically, the matrix phase, which is a three-dimensional network structure of a silicon-oxygen skeleton, and the silicon particles are mixed and homogenized, and then the solvent is removed, dried, and treated at a high temperature to obtain an intermediate.
[0045] The polysiloxane compound may be, for example, a resin containing at least one of a polycarbosilane structure, a polysilazane structure, a polysilane structure, and a polysiloxane structure. The resin may be a resin containing only these structures, or a composite resin having at least one of these structures as a segment and chemically bonded to other polymer segments. The form of the composite may be graft copolymerization, block copolymerization, random copolymerization, alternating copolymerization, etc. For example, a composite resin having a graft structure in which a polysiloxane segment is chemically bonded to the side chain of a polymer segment, or a composite resin having a block structure in which a polysiloxane segment is chemically bonded to the end of a polymer segment may be mentioned.
[0046] The polysiloxane segment is preferably a polysiloxane compound having a structural unit represented by the following general formula (S-1) and / or the following general formula (S-2): In particular, the polysiloxane compound more preferably has a carboxy group, an epoxy group, an amino group, or a polyether group on the side chain or terminal of the siloxane bond (Si-O-Si) main skeleton.
[0047] [ka]
[0048] [ka]
[0049] In the above general formulas (S-1) and (S-2), R 1 R represents an aromatic hydrocarbon group, an alkyl group, an epoxy group, a carboxy group, or the like, which may have a substituent. 2 and R 3 respectively represent an alkyl group, a cycloalkyl group, an aryl group, an aralkyl group, an epoxy group, a carboxy group, or the like.
[0050] Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a 1-methylbutyl group, a 2-methylbutyl group, a 1,2-dimethylpropyl group, a 1-ethylpropyl group, a hexyl group, an isohexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 1,1-dimethylbutyl group, a 1,2-dimethylbutyl group, a 2,2-dimethylbutyl group, a 1-ethylbutyl group, a 1,1,2-trimethylpropyl group, a 1,2,2-trimethylpropyl group, a 1-ethyl-2-methylpropyl group, a 1-ethyl-1-methylpropyl group, etc. Examples of the cycloalkyl group include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, and a cyclohexyl group.
[0051] Examples of the aryl group include a phenyl group, a naphthyl group, a 2-methylphenyl group, a 3-methylphenyl group, a 4-methylphenyl group, a 4-vinylphenyl group, and a 3-isopropylphenyl group.
[0052] Examples of the aralkyl group include a benzyl group, a diphenylmethyl group, and a naphthylmethyl group.
[0053] Examples of polymer segments other than the polysiloxane segment contained in the polysiloxane compound include vinyl polymer segments such as acrylic polymers, fluoroolefin polymers, vinyl ester polymers, aromatic vinyl polymers, and olefin polymers, as well as polymer segments such as urethane polymer segments, ester polymer segments, and ether polymer segments. Among these, vinyl polymer segments are preferred.
[0054] The polysiloxane compound may be a composite resin in which a polysiloxane segment and a polymer segment are bonded in a structure represented by the following structural formula (S-3), or may have a three-dimensional network polysiloxane structure.
[0055] [ka]
[0056] In the formula, the carbon atom is a carbon atom that constitutes a polymer segment, and the two silicon atoms are silicon atoms that constitute a polysiloxane segment.
[0057] The polysiloxane segment of the polysiloxane compound may have a functional group capable of reacting by heating, such as a polymerizable double bond, in the polysiloxane segment. By subjecting the polysiloxane compound to heat treatment before thermal decomposition, a crosslinking reaction progresses and the compound is solidified, which makes it easy to carry out the thermal decomposition treatment.
[0058] Examples of the polymerizable double bond include a vinyl group and a (meth)acryloyl group. The number of polymerizable double bonds in the polysiloxane segment is preferably 2 or more, more preferably 3 to 200, and even more preferably 3 to 50. In addition, by using a composite resin having 2 or more polymerizable double bonds as the polysiloxane compound, the crosslinking reaction can be easily promoted.
[0059] The polysiloxane segment may have a silanol group and / or a hydrolyzable silyl group. Examples of the hydrolyzable group in the hydrolyzable silyl group include a halogen atom, an alkoxy group, a substituted alkoxy group, an acyloxy group, a phenoxy group, a mercapto group, an amino group, an amide group, an aminooxy group, an iminoxy group, and an alkenyloxy group. The hydrolyzable silyl group becomes a silanol group by hydrolysis of these groups. In parallel with the thermosetting reaction, a hydrolysis condensation reaction proceeds between the hydroxyl group in the silanol group and the hydrolyzable group in the hydrolyzable silyl group, thereby obtaining a solid polysiloxane compound.
[0060] The silanol group in the present invention is a silicon-containing group having a hydroxyl group directly bonded to a silicon atom. The hydrolyzable silyl group in the present invention is a silicon-containing group having a hydrolyzable group directly bonded to a silicon atom, and specifically includes, for example, a group represented by the following general formula (S-4).
[0061] [ka]
[0062] In the formula, R 4 R represents a monovalent organic group such as an alkyl group, an aryl group, or an aralkyl group. 5 is a halogen atom, an alkoxy group, an acyloxy group, an allyloxy group, a mercapto group, an amino group, an amido group, an aminooxy group, an iminoxy group or an alkenyloxy group, and b is an integer of 0 to 2.
[0063] Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a 1-methylbutyl group, a 2-methylbutyl group, a 1,2-dimethylpropyl group, a 1-ethylpropyl group, a hexyl group, an isohexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 1,1-dimethylbutyl group, a 1,2-dimethylbutyl group, a 2,2-dimethylbutyl group, a 1-ethylbutyl group, a 1,1,2-trimethylpropyl group, a 1,2,2-trimethylpropyl group, a 1-ethyl-2-methylpropyl group, and a 1-ethyl-1-methylpropyl group.
[0064] Examples of the aryl group include a phenyl group, a naphthyl group, a 2-methylphenyl group, a 3-methylphenyl group, a 4-methylphenyl group, a 4-vinylphenyl group, and a 3-isopropylphenyl group.
[0065] Examples of the aralkyl group include a benzyl group, a diphenylmethyl group, and a naphthylmethyl group.
[0066] Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.
[0067] Examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a butoxy group, a sec-butoxy group, and a tert-butoxy group.
[0068] Examples of the acyloxy group include a formyloxy group, an acetoxy group, a propanoyloxy group, a butanoyloxy group, a pivaloyloxy group, a pentanoyloxy group, a phenylacetoxy group, an acetoacetoxy group, a benzoyloxy group, and a naphthoyloxy group.
[0069] The allyloxy group includes, for example, a phenyloxy group and a naphthyloxy group.
[0070] Examples of the alkenyloxy group include a vinyloxy group, an allyloxy group, a 1-propenyloxy group, an isopropenyloxy group, a 2-butenyloxy group, a 3-butenyloxy group, a 2-pentenyloxy group, a 3-methyl-3-butenyloxy group, and a 2-hexenyloxy group.
[0071] Examples of the polysiloxane segment having the structural unit represented by the above general formula (S-1) and / or the above general formula (S-2) include those having the following structures.
[0072] [ka]
[0073] [ka]
[0074] [ka]
[0075] R in the above structural formulas (1) to (3) 6 is the above R 1 In addition, R in the above structural formulas (4) to (8) has the same meaning as 7 and R 8 are the above R 2 and R 3 It has the same meaning as:
[0076] The polymer segment may have various functional groups as necessary within the scope of not impairing the effects of the present invention. Examples of such functional groups include a carboxyl group, a blocked carboxyl group, a carboxylic anhydride group, a tertiary amino group, a hydroxyl group, a blocked hydroxyl group, a cyclocarbonate group, an epoxy group, a carbonyl group, a primary amide group, a secondary amide group, a carbamate group, and a functional group represented by the following structural formula (S-5).
[0077] [ka]
[0078] The polymer segment may also have a polymerizable double bond such as a vinyl group or a (meth)acryloyl group.
[0079] The polysiloxane compound is preferably produced, for example, by the following methods (1) to (3).
[0080] (1) A method in which a polymer segment containing a silanol group and / or a hydrolyzable silyl group is prepared in advance as a raw material for the polymer segment, and this polymer segment is mixed with a silane compound having both a silanol group and / or a hydrolyzable silyl group and a polymerizable double bond to carry out a hydrolysis condensation reaction.
[0081] (2) A method in which a polymer segment containing a silanol group and / or a hydrolyzable silyl group is prepared in advance as a raw material for the polymer segment. A polysiloxane is also prepared in advance by subjecting a silane compound having both a silanol group and / or a hydrolyzable silyl group and a polymerizable double bond to a hydrolysis and condensation reaction. The polymer segment and the polysiloxane are then mixed together to carry out a hydrolysis and condensation reaction.
[0082] (3) A method of mixing a polymer segment, a silane compound having a silanol group and / or a hydrolyzable silyl group, and a polymerizable double bond, and a polysiloxane, and carrying out a hydrolysis condensation reaction, which produces a polysiloxane compound.
[0083] Alternatively, commercially available polysiloxane compounds may be used, such as the Ceranate (registered trademark) series (organic / inorganic hybrid coating resin; manufactured by DIC Corporation) and Compoceran SQ series (silsesquioxane hybrid; manufactured by Arakawa Chemical Industries, Ltd.).
[0084] In order to obtain a polysiloxane resin having a silicon-oxygen-carbon skeleton, a carbon source resin having good miscibility with the polysiloxane compound may be used together with the polysiloxane compound. Examples of such carbon source resins include thermosetting resins and thermoplastic resins that include a molecular structure having a benzene ring or an aromatic functional group.
[0085] Examples of thermosetting resins include phenolic resins such as novolac type phenolic resins and resol type phenolic resins; epoxy resins such as bisphenol type epoxy resins and novolac type epoxy resins; melamine resins; urea resins; aniline resins; cyanate resins; furan resins; ketone resins; unsaturated polyester resins; and urethane resins.
[0086] Furthermore, the thermoplastic resin is not particularly limited, and examples thereof include polyethylene, polystyrene, polyacrylonitrile, acrylonitrile-styrene (AS) resin, acrylonitrile-butadiene-styrene (ABS) resin, polypropylene, vinyl chloride, methacrylic resin, polyethylene terephthalate, polyamide, polycarbonate, polyacetal, polyphenylene ether, polybutylene terephthalate, polyphenylene sulfide, polysulfone, polyethersulfone, polyetheretherketone, polyetherimide, polyamideimide, polyimide, and polyphthalamide.
[0087] Then, the solvent is removed, dried, and treated at high temperature to obtain an intermediate derived from a polysiloxane resin containing silicon particles. Drying is performed, for example, with a dryer, a vacuum dryer, a spray dryer, or the like. The drying temperature is preferably 80°C or higher, and preferably 150°C or lower. Drying may be performed while reducing the pressure. The high-temperature treatment is performed according to a firing program that is specified by the heating rate, the holding time at a constant temperature, and the like. The treatment temperature is preferably, for example, a maximum reaching temperature of 1000°C or higher. The treatment device can be appropriately selected from among a fluidized bed reactor, a rotary furnace, a vertical moving bed reactor, a tunnel furnace, a batch furnace, a rotary kiln, and the like, depending on the purpose.
[0088] (Process 1) Next, at least one metal element compound selected from the group consisting of Li, K, Na, Ca, Mg, and Al is mixed with the intermediate derived from the polysiloxane resin containing silicon particles obtained above (mixing step). Note that, in the description of step 1 below, some steps may be omitted, and there is no particular restriction on the mixing method.
[0089] The metal element compound is not particularly limited as long as it contains the above-mentioned elements, and metal element compounds such as oxides, hydroxides, oxyhydroxides, nitrates, oxalates, acetates, and carbonates can be used. Specifically, when the metal element is Li, lithium oxide and anhydrous lithium acetate are typical examples, and when the metal element is Mg, anhydrous magnesium acetate is typical examples. In this embodiment, when the metal element is Li, anhydrous lithium acetate is preferable, and when the metal element is Mg, anhydrous magnesium acetate is preferable. These metal element compounds may be added by dispersing them in a suitable organic solvent (polar or non-polar) such as ethanol, MEK, etc. The amount of the metal element compound added is preferably 0.1 to 30% by mass based on the total mass of the composite particles.
[0090] After adding the metal element compound, mixing is performed to uniformly disperse the metal element in the intermediate derived from the polysiloxane resin. The mixing method can be performed, for example, with a stirrer equipped with a stirring blade, and the stirring time is, for example, 1 minute to 2 hours, preferably 2 minutes to 1 hour. The stirring may be performed at room temperature, or may be performed while heating to about 30 to 50°C. In addition, instead of dispersing in an organic solvent and then mixing, the powdered metal element compound may be added directly to the intermediate derived from the polysiloxane resin and mixed. In the case of mixing in powder form, it can be performed with a ball mill or a bead mill, and the mixing time is, for example, 1 minute to 2 hours, preferably 2 minutes to 1 hour. The stirring may be performed at room temperature, or may be performed while heating to about 30 to 50°C.
[0091] After the mixing in step 1, the solvent is removed and the mixture is dried. The solvent can be removed by a common method such as filtration. The drying can be performed, for example, using a dryer, a vacuum dryer, a spray dryer, or the like. The drying temperature is preferably 80°C or higher and 150°C or lower. Drying may be performed under reduced pressure.
[0092] (Process 2) After the drying, the mixture is fired at 900°C or less in an oxygen-free atmosphere (firing step). The firing apparatus can be appropriately selected from among fluidized bed reactors, rotary furnaces, vertical moving bed reactors, tunnel furnaces, batch furnaces, rotary kilns, etc. depending on the purpose. The firing is performed according to a firing program that is defined by the heating rate, holding time at a constant temperature, etc. The firing temperature is preferably, for example, a maximum reaching temperature of 900°C or less. This results in composite particles that contain the metal element of the metal element compound added in the mixing step as a compound.
[0093] The non-oxidizing atmosphere during the firing is not particularly limited with respect to the type of gas used, and examples thereof include nitrogen, argon, hydrogen, and a mixed gas of nitrogen and hydrogen.
[0094] The fired product obtained above may be further pulverized and classified as necessary. The pulverization may be performed in one step until the desired particle size is obtained, or may be performed in several steps. In addition, when the particle size is 10 mm or more, the particles may be coarsely pulverized using a jaw crusher, roll crusher, etc., and then pulverized using a glow mill, ball mill, etc., and may be further pulverized using a bead mill, jet mill, etc. Classification may be performed using an air classifier, wet classifier, etc.
[0095] The composite particles thus obtained may be used as they are as the negative electrode active material for secondary batteries. When the negative electrode active material for secondary batteries further has carbon (carbon coating) on the surface, the obtained active material is coated with a carbon coating in a chemical vapor deposition apparatus at a temperature range of 700°C to 1000°C in a flow of a pyrolytic carbon source gas and a carrier inert gas. Examples of pyrolytic carbon source gas include acetylene, ethylene, acetone, alcohol, propane, methane, and ethane. Examples of inert gas include nitrogen, helium, and argon, and nitrogen is usually used.
[0096] In the method for producing composite particles of this embodiment, a metal element compound may be added to the intermediate after the high-temperature treatment, and the mixture may be mixed and fired, or a metal element compound may be added to an intermediate that has not been subjected to high-temperature treatment, and the mixture may be mixed and fired. Furthermore, the composite particles obtained by firing may be washed with a liquid in order to remove impurities and unreacted substances, and the liquid is preferably one having an OH group, such as water or alcohol.
[0097] [Negative electrode] The negative electrode of this embodiment is not particularly limited as long as it contains the above-mentioned negative electrode active material for secondary batteries, but may also contain other components such as an organic binder and a conductive assistant. The negative electrode of this embodiment can be produced by applying a slurry containing the composite particles of this embodiment, an organic binder, and other components such as conductive assistants as necessary, onto a copper foil current collector in the form of a thin film. The negative electrode can also be produced by adding a carbon material such as graphite to the slurry. Examples of the carbon material include natural graphite, artificial graphite, and amorphous carbon such as hard carbon or soft carbon.
[0098] For example, the negative electrode active material for secondary batteries and a binder, which is an organic binding material, are kneaded together with a solvent using a dispersing device such as a stirrer, a ball mill, a super sand mill, or a pressure kneader to prepare a negative electrode material slurry, which is then applied to a current collector to form a negative electrode layer. Alternatively, the negative electrode material paste slurry can be formed into a sheet, pellet, or other shape and integrated with a current collector.
[0099] Examples of the organic binder include styrene-butadiene rubber copolymers (hereinafter also referred to as "SBR"); ethylenically unsaturated carboxylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, (meth)acrylonitrile, and hydroxyethyl (meth)acrylate, and unsaturated carboxylic acid copolymers such as (meth)acrylic copolymers consisting of ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid, and maleic acid; and polymer compounds such as polyvinylidene fluoride, polyethylene oxide, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polyimide, polyamideimide, and carboxymethylcellulose (hereinafter also referred to as "CMC").
[0100] Depending on their physical properties, these organic binders may be dispersed or dissolved in water, or dissolved in an organic solvent such as N-methyl-2-pyrrolidone (NMP), etc. The content of the organic binder in the negative electrode layer of the lithium ion secondary battery negative electrode is preferably 1 mass % to 30 mass %, more preferably 2 mass % to 20 mass %, and even more preferably 3 mass % to 15 mass %.
[0101] When the content of the organic binder is 1% by mass or more, the adhesion is better and the destruction of the negative electrode structure due to the expansion and contraction during charging and discharging is more suppressed, whereas when the content is 30% by mass or less, the increase in the electrode resistance is more suppressed.
[0102] In addition, the negative electrode material slurry may be mixed with a conductive assistant as necessary. Examples of the conductive assistant include carbon black, graphite, acetylene black, and oxides and nitrides that exhibit conductivity. The amount of the conductive assistant may be, for example, 1% by mass to 15% by mass with respect to the negative electrode active material of this embodiment.
[0103] The material and shape of the current collector may be, for example, copper, nickel, titanium, stainless steel, or the like, in the form of a foil, a perforated foil, a mesh, or a strip. Porous materials such as porous metal (foamed metal) and carbon paper can also be used.
[0104] Examples of the method for applying the negative electrode material slurry to the current collector include metal mask printing, electrostatic coating, dip coating, spray coating, roll coating, doctor blade, gravure coating, screen printing, etc. After application, it is preferable to perform rolling treatment using a flat plate press, a calendar roll, etc. as necessary.
[0105] The negative electrode material slurry may be formed into a sheet or pellet shape, and this may be integrated with a current collector by, for example, rolling, pressing, or a combination of these.
[0106] The negative electrode layer formed on the current collector or the negative electrode layer integrated with the current collector is preferably heat-treated according to the organic binder used. For example, when a water-based styrene-butadiene rubber copolymer (SBR) is used, the heat treatment may be performed at 100 to 130°C, and when an organic binder having a polyimide or polyamideimide as the main skeleton is used, the heat treatment is preferably performed at 150 to 450°C.
[0107] This heat treatment removes the solvent, hardens the binder, and increases the strength, improving the adhesion between the particles and between the particles and the current collector. It is preferable to carry out these heat treatments in an inert atmosphere such as helium, argon, or nitrogen, or in a vacuum atmosphere, in order to prevent oxidation of the current collector during the treatment.
[0108] In addition, it is preferable to subject the negative electrode to pressure treatment after the heat treatment. 3 from 1.8 g / cm 3 and preferably 1.1 g / cm 3 to 1.7 g / cm 3 More preferably, it is 1.2 g / cm 3 from 1.6 g / cm 3 It is more preferable that the electrode density is higher. The higher the electrode density, the more the adhesion and the volumetric capacity density of the electrode tend to improve. On the other hand, if the electrode density is too high, the voids in the electrode are reduced, which weakens the effect of suppressing the volumetric expansion of silicon and the like, and the capacity retention rate may decrease. Therefore, the optimal range of the electrode density is selected.
[0109] [Secondary battery] The secondary battery of the present embodiment includes the negative electrode of the present embodiment. As the secondary battery, non-aqueous electrolyte secondary batteries and solid electrolyte secondary batteries are preferable, and the negative electrode of the present embodiment exhibits excellent performance particularly when used as the negative electrode of a non-aqueous electrolyte secondary battery.
[0110] When the secondary battery of the present embodiment is used, for example, as a wet electrolyte secondary battery, it can be constructed by disposing a positive electrode and a negative electrode containing the negative electrode active material for a secondary battery of the present embodiment opposite each other with a separator interposed therebetween and injecting an electrolyte solution.
[0111] The positive electrode can be obtained by forming a positive electrode layer on the surface of a current collector in the same manner as the negative electrode. In this case, the current collector can be a strip of a metal or alloy such as aluminum, titanium, or stainless steel in the form of a foil, a perforated foil, a mesh, or the like.
[0112] There are no particular limitations on the positive electrode material used in the positive electrode layer. When preparing a lithium ion secondary battery among non-aqueous electrolyte secondary batteries, for example, a metal compound, metal oxide, metal sulfide, or conductive polymer material capable of doping or intercalating lithium ions may be used. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and composite oxides thereof (LiCoxNiyMnzO2, x+y+z=1), lithium manganese spinel (LiMn2O4), lithium vanadium compounds, V2O5, V6O 13 , VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, olivine-type LiMPO4 (wherein M is Co, Ni, Mn, or Fe), conductive polymers such as polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene, porous carbon, etc. can be used alone or in combination.
[0113] The separator may be a nonwoven fabric, cloth, microporous film, or a combination thereof, mainly composed of polyolefin such as polyethylene or polypropylene. If the positive electrode and the negative electrode of the nonaqueous electrolyte secondary battery are not in direct contact with each other, it is not necessary to use a separator.
[0114] As the electrolyte, for example, a so-called organic electrolyte can be used in which a lithium salt such as LiClO4, LiPF6, LiAsF6, LiBF4, or LiSO3CF3 is dissolved in a non-aqueous solvent such as ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, cyclopentanone, sulfolane, 3-methylsulfolane, 2,4-dimethylsulfolane, 3-methyl-1,3-oxazolidin-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, butyl methyl carbonate, ethyl propyl carbonate, butyl ethyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, or ethyl acetate, either alone or as a mixture of two or more components.
[0115] The structure of the secondary battery of this embodiment is not particularly limited, but usually, the positive electrode, the negative electrode, and a separator provided as necessary are wound into a flat spiral shape to form a wound electrode plate group, or these are stacked in a flat plate shape to form a stacked electrode plate group, and these electrode plate groups are generally sealed in an exterior body. Note that the half cell used in the examples of the present invention is mainly composed of the negative electrode active material, and a simple evaluation is performed using metallic lithium as the counter electrode, but this is for the purpose of more clearly comparing the cycle characteristics of the active material itself.
[0116] The secondary battery of the present embodiment is not particularly limited, but is used as a paper type battery, a button type battery, a coin type battery, a laminated type battery, a cylindrical type battery, a square type battery, etc. The above-mentioned negative electrode active material of the present embodiment can also be applied to electrochemical devices in general that use insertion and desorption of lithium ions as a charge / discharge mechanism, such as hybrid capacitors and solid lithium secondary batteries. EXAMPLES
[0117] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the present examples, [%] and [parts] represent "mass%" and "mass parts" unless otherwise specified. Silicon particles were obtained by the following method, composite particles were prepared, and secondary battery evaluation was performed.
[0118] (Preparation of silicon particles) Synthesis Example 1 In a 150ml container of a small bead mill device, zirconia beads with a particle size of 0.1 mm and 100m of methyl ethyl ketone (hereinafter also referred to as "MEK") solvent were placed at a filling rate of 60%. Silicon powder with an average particle size of 5 μm and a cationic dispersant liquid (BYK Japan Co., Ltd.: BYK145) were then placed in the container, and wet grinding was performed in the bead mill at a rotation speed of 1500 revolutions / min for a grinding time of 4 hours, resulting in a dark brown liquid-like silicon slurry with a solid concentration of 30% by mass. The morphology and size of the obtained silicon particles were confirmed by TEM observation, and the average particle size of the silicon particles was 50 nm.
[0119] (Preparation and evaluation of composite particles) Example 1 The silicon particles (average particle size = 50 nm) prepared in the above Synthesis Example 1 were mixed with polysiloxane resin (CERANATE SSA-500: manufactured by DIC Corporation) so that the silicon element content after high-temperature firing with the silicon slurry was 50%, and the solvent was removed in a nitrogen atmosphere in an oil bath at 120 ° C., and reduced pressure drying was performed at 110 ° C. for 10 hours to obtain a mixed dried product. Next, the mixed dried product was fired at a high temperature at 1100 ° C. / 6 hours in a nitrogen atmosphere to obtain a black fired product. Then, the black fired product was pulverized with a planetary ball mill (ball mill P-6 classic line: manufactured by FRITSCH) to obtain a composite particle intermediate. Lithium oxide (LiO2) (manufactured by Wako Pure Chemical Industries, Ltd.) was added to the prepared composite particle intermediate in an amount of 0.1 equivalent to the silicon particles, and mixed with a planetary ball mill. The mixture was sintered at high temperature at 800°C for 2 hours in a nitrogen atmosphere, washed with distilled water, and dried under reduced pressure to obtain a powder with an average particle size of 6.4 μm and a specific surface area (SSA) of 5.1 m. 2 / g of composite particles were obtained. The amount of metal ion elements relative to the total mass of the obtained composite particles was measured using an ICP-OES analyzer (ICAP-7400, manufactured by Thermo Fisher Scientific Co., Ltd.), and the amount of metal elements present was 4.2% by mass. The metal ion element concentration distribution ratio between the surface and interior of the composite particle was measured by Auger electron spectroscopy (AES). As a result, A / (A+B) was 0.9, where A is the ratio of metal ion elements to all elements in a region 30% from the particle surface toward the inside, and B is the ratio of metal ion elements to all elements in the other regions. Identification of metal silicate species and measurement of crystallite size and intensity ratio were performed using an XRD device (Ultima5: manufactured by Rigaku Co., Ltd.) and calculated using Scherrer's formula based on the half-width of the diffraction peaks (2θ=28.4°, 26.9°) belonging to the silicon (111) crystal plane and Li2SiO3 (111) crystal plane from the results of Cu-Ka radiation. The Si crystallite size was 22 nm, the Li2SiO3 crystallite size was 21 nm, and the peak intensity ratio (D / C) was 0.28. A half-cell was evaluated to measure the initial efficiency and cycle characteristics of the electrode. The composite particles (8 parts) obtained above were mixed with acetylene black (1 part) as a conductive additive and an organic binder (1 part, consisting of SBR (0.75 parts) + CMC (0.25 parts)) and stirred for 10 minutes in a rotating and revolving type foaming blender to prepare a slurry. After applying the coating to a copper foil with a thickness of 20 μm using an applicator, the film was dried under reduced pressure at 110°C to obtain a thin electrode film. A circular electrode with a diameter of 14 mm was punched out and pressed using a tablet press to a thickness of approximately 40 μm. The thickness was measured by calculating the average value of five points on the electrode using a thickness gauge. In a dry room with extremely low moisture content (dew point -40°C or less), Li foil was placed opposite the electrode of the present invention via a 25μm polypropylene separator, and an electrolyte (Kishida Chemical Co., Ltd., 1mol / L LiPF6, diethyl carbonate: ethylene carbonate = 1:1 (capacity ratio)) was adsorbed to prepare an evaluation half battery (CR2032 type). The battery characteristics were measured using a secondary battery charge / discharge tester (Hokuto Denko Co., Ltd.), and an evaluation test of the charge / discharge characteristics was performed under the set conditions of constant current / low voltage charge / discharge / constant current charge / discharge at room temperature of 25°C, cutoff voltage range of 0.005-1.5V, and charge rate of 0.1C (1-3 times) and 0.2C (after 4 cycles). The initial efficiency was 86%. In order to evaluate the atmospheric stability of the samples, composite particles stored in a vial at room temperature in the atmosphere were evaluated using a half cell. The initial efficiency of the sample stored in the atmosphere for 7 days was 85%, and the initial efficiency of the sample stored in the atmosphere for 14 days was also 85%. For the evaluation of the full cell, a positive electrode film was prepared using a single-layer sheet of LiCoO2 as the positive electrode active material and aluminum foil as the current collector, and a negative electrode film was prepared by mixing graphite powder, active material powder, and binder with a design value of 450mAh / g discharge capacity. A non-aqueous electrolyte solution was used in which lithium hexafluorophosphate was dissolved at a concentration of 1mol / L in a 1 / 1 volumetric mixture of ethylene carbonate and diethyl carbonate, and a laminated lithium ion secondary battery was prepared using a 30μm thick polyethylene microporous film as a separator. The laminated lithium ion secondary battery was charged at a constant current of 1.2mA (0.25c based on the positive electrode) at room temperature until the voltage of the test cell reached 4.2V, and after reaching 4.2V, the current was reduced to keep the cell voltage at 4.2V and the discharge capacity was calculated. The capacity retention rate at room temperature for 300 cycles was 89%.
[0120] Example 2 A polysiloxane resin (CERANATE SSA-934: manufactured by DIC Corporation) and a phenolic resin (SUMILITE RESIN: PR-53570, manufactured by Sumitomo Bakelite Co., Ltd.) were thoroughly mixed in a stirrer at a resin solid matter weight composition ratio (5:5), and mixed with the silicon slurry so that the silicon element content after high-temperature firing was 50%, to produce a mixed and dried product. The procedure was the same as in Example 1, except that when the Li source was added, the amount of LiO added was 0.05 equivalents relative to the silicon particles.
[0121] Example 3 The same procedure as in Example 2 was repeated, except that the amount of Li2O added was 0.2 equivalents relative to the silicon particles.
[0122] Example 4 The same procedure as in Example 1 was repeated except that the amount of Li2O added was 0.1 equivalent relative to the silicon particles and the firing temperature was 800°C / 1 h.
[0123] Example 5 The same procedure as in Example 2 was repeated except that Li2O was changed to Li2CO3, the amount added was 1.0 equivalent relative to the silicon particles, and the firing temperature was 800°C / 4h.
[0124] Example 6 The same procedure as in Example 2 was repeated except that the amount of Li2O added was 0.07 equivalent relative to the silicon particles and the firing temperature was 800°C / 1 h.
[0125] Example 7 The same procedure as in Example 2 was repeated except that the amount of Li2O added was 0.25 equivalents relative to the silicon particles and the firing temperature was 800°C for 6 hours.
[0126] Example 8 The same procedure as in Example 2 was repeated except that the amount of Li2O added was 0.3 equivalents relative to the silicon particles and the firing temperature was 800°C for 4 hours.
[0127] Example 9 The black fired product was ground in a planetary ball mill at 220 rpm for 10 minutes, and the procedure was the same as in Example 2, except that the amount of Li2O added was 0.5 equivalents relative to the silicon particles and the firing temperature was 800°C for 6 hours.
[0128] Example 10 The same procedure as in Example 2 was repeated, except that the amount of Li2O added was 0.4 equivalents relative to the silicon particles, and the firing temperature was other than 700°C / 6h.
[0129] Example 11 The same procedure as in Example 2 was repeated except that the amount of Li2O added was 0.5 equivalents relative to the silicon particles and the firing temperature was 900°C for 2 hours.
[0130] Example 12 The same procedure as in Example 2 was repeated except that the amount of Li2O added was 0.1 equivalent relative to the silicon particles and the firing temperature was 800°C for 24 hours.
[0131] Example 13 The same procedure as in Example 2 was repeated, except that Li2O was changed to Na2CO3 and the amount was 0.5 equivalent to the silicon particles.
[0132] Example 14 The same procedure as in Example 2 was repeated, except that Li2O was changed to K2CO3 and the amount was 0.5 equivalent to the silicon particles.
[0133] Comparative Example 1 The same procedure was carried out as in Example 2, except that Li2O was not added.
[0134] Comparative Example 2 The same procedure as in Example 2 was repeated except that no polysiloxane resin or phenol resin was used, the amount of Li2O added was 0.1 equivalent relative to the silicon particles, and the firing temperature was 800°C for 2 hours.
[0135] Comparative Example 3 The same procedure as in Example 2 was repeated except that no silicon particles were used and the amount of Li2O added was 0.3 equivalents to the material after sintering at 1100°C for 6 hours.
[0136] Comparative Example 4 The same procedure as in Example 2 was repeated, except that Li2O was changed to Fe2O3, the amount of Fe2O3 added was 0.1 equivalent relative to the silicon particles, and the firing temperature was 800°C for 2 hours.
[0137] [Table 1]
[0138] From the above Table 1, it can be seen that the composite particles of the present invention (Examples 1 to 14) have higher capacity retention and initial (coulombic) efficiency when used in a secondary battery, and there is almost no decrease in initial efficiency when stored in air for a long period of time, compared to Comparative Examples 1 to 4. Therefore, it was demonstrated that the composite particles of the present invention can maintain high charge / discharge performance, such as capacity retention and initial coulombic efficiency, in a secondary battery.
Claims
1. A composite particle comprising at least one silicon particle and a matrix phase outside the silicon particle, further comprising a silicate compound containing a metal element, the matrix phase having a three-dimensional network structure of a silicon-oxygen skeleton optionally containing a nitrogen element or a three-dimensional network structure of a silicon-oxygen-carbon skeleton optionally containing a nitrogen element, the metal element being at least one selected from the group consisting of Li, K, Na, Ca, Mg and Al, Composite particles in which, when a ratio A (atom %) of a metal ion element to all elements present in a region 30% inward from the surface of the composite particle is defined as A, and a ratio B (atom %) of the metal ion element to all elements present in the other region is defined as B, the metal ion element abundance ratio satisfies 0.5<A / (A+B)<1.
0.
2. 2. The composite particle according to claim 1, wherein the metal ion element concentration of the metal element is 0.1 to 40.0 atom % based on the total elements of the composite particle.
3. The composite particle according to claim 1 , wherein the silicate compound contains Li element.
4. The composite particle according to claim 3 , wherein the silicate compound has a crystal structure represented by Li x Si y O z (wherein x, y, and z are integers greater than 0).
5. The composite particle according to claim 4, wherein the silicate compound has a crystal structure represented by LixSiyOz (where x+4y-2z=0).
6. The composite particle according to claim 5, wherein the silicate compound comprises at least one crystal structure selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5.
7. The composite particle according to claim 1 , wherein the Li element is contained in an amount of 20 mass % or less based on the total mass of the composite particle.
8. The composite particle according to claim 1, wherein a peak intensity C corresponding to the (111) plane of the silicon particle in the X-ray diffraction spectrum of the silicon particle and a peak intensity D corresponding to the (111) plane in the X-ray diffraction spectrum of Li2SiO3 satisfy 0 < D / C ≦ 0.
6.
9. 2. The composite particle according to claim 1, wherein in the X-ray diffraction spectrum of the silicon particle, at a peak where 2θ corresponds to the (111) plane of the silicon particle, the crystallite size x satisfies 10 nm < x < 30 nm, and in the X-ray diffraction peak corresponding to the (111) plane of Li2SiO3, the crystallite size y satisfies 1 nm < y < 40 nm.
10. 2. The composite particle according to claim 1, wherein the average particle diameter x is 1 μm<x<15 μm and the specific surface area n is 0.1 m2 / g<n<20 m2 / g.
11. The composite particle according to claim 1 , wherein the matrix phase contains C element in addition to Si and O elements.
12. A method for producing the composite particle according to claim 1, comprising the following steps 1 and 2: Step 1: A step of mixing at least one metal element compound selected from the group consisting of Li, K, Na, Ca, Mg, and Al with an intermediate derived from a polysiloxane resin containing silicon particles. Step 2: Firing at 900° C. or less in a non-oxygen atmosphere
13. A negative electrode active material for a secondary battery, comprising the composite particle according to any one of claims 1 to 11.
14. A negative electrode comprising the negative electrode active material for a secondary battery according to claim 13.
15. A secondary battery comprising the negative electrode according to claim 14.
Citation Information
Patent Citations
Nonaqueous electrolyte battery and negative active material
JP2007059213A
Negative electrode material for nonaqueous secondary battery and method for producing the material, and lithium ion secondary battery
JP2011222151A
Negative electrode material, method of producing the negative electrode material, and mixed negative electrode material
JP2018152250A
Negative electrode active material for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery, and manufacturing method of negative electrode material for nonaqueous electrolyte secondary battery
JP2020113495A
Anode active material, anode including the anode active material, and secondary battery including the anode
JP2022125285A